Fuzzy Sliding Mode Control of DC-DC Boost Converter - Duranay, Zeynep Bala; Guldemir, Hanifi; Tuncer, Servet (Eos Assoc, 2018)
A sliding mode fuzzy control method which combines sliding mode and fuzzy logic control for DC-DC boost converter is designed to achieve robustness and better performance. A fuzzy sliding mode controller in which sliding surface whose reference is obtained from the output of the outer voltage loop is used to control the inductor current. A linear PI controller is used for the outer voltage loop. The control system is simulated using Matlab/Simulink. The simulation results are presented for input voltage and load variations. Simulated results are given to show the effectiveness of the control system.
Keywords: boost converter; DC-DC converter; FLC; fuzzy logic; sliding mode